2022
DOI: 10.3390/ijerph192315636
|View full text |Cite
|
Sign up to set email alerts
|

Functioning Problems Associated with Health Conditions with Greatest Disease Burden in South Africa: A Scoping Review

Abstract: A notable rise in health-related disability for which evidence-based rehabilitation is beneficial is evident in low-to-middle income countries. This scoping review aimed to systematically identify and map the most common functioning problems associated with health conditions that contribute most to disability in South Africa using the International Classification of Functioning, Disability and Health (ICF) framework. Peer-reviewed evidence published from January 2006 to December 2021 was systematically searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 292 publications
0
2
0
Order By: Relevance
“…One of the first qualitative studies to investigate the QOL change beyond 1 year after ART initiation, conducted in South African PWH in the public sector, suggests that changes in QOL and associated problems continue to occur in the longer term (Hanass-Hancock et al 2015 ). Our findings furthermore echo a recent scoping review, which identified problems related to mobility, pain, and mental health as the most common functioning problems contributing to disability in South African adults across various health conditions (including HIV) (Charumbira, Berner & Louw 2022 ). These findings may have significant economic and social implications, given the increasing longevity of PWH because of advanced care.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…One of the first qualitative studies to investigate the QOL change beyond 1 year after ART initiation, conducted in South African PWH in the public sector, suggests that changes in QOL and associated problems continue to occur in the longer term (Hanass-Hancock et al 2015 ). Our findings furthermore echo a recent scoping review, which identified problems related to mobility, pain, and mental health as the most common functioning problems contributing to disability in South African adults across various health conditions (including HIV) (Charumbira, Berner & Louw 2022 ). These findings may have significant economic and social implications, given the increasing longevity of PWH because of advanced care.…”
Section: Discussionsupporting
confidence: 85%
“…Findings in these studies suggest that PWH with impaired mobility function may also have worse QOL. This is of particular concern considering that in South Africa, at least 70% of adults seeking primary care have one or more functioning problem(s) and HIV counts among the top 10 diseases contributing to disability in the country (Charumbira, Berner & Louw 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another significant problem affecting the receipt of quality rehabilitation services was the lack of assistive mobility devices. This problem causes challenges for these populations, where mobility-related functioning problems impact their livelihood significantly [ 5 ]. In these poorer populations it may not be possible to source assistive devices, even from private.…”
Section: Discussionmentioning
confidence: 99%
“…The need is more significant in South Africa's healthcare system, which must cope with the quadruple burden of disease arising from communicable diseases such as HIV and Tuberculosis (TB), maternal and child mortality, injury and trauma, and non-communicable disease (NCDs) [ 4 ]. The health conditions contributing to greatest disease burden in South Africa are associated with significant functioning problems related to mobility, pain and mental health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%